Comparison of spinal sagittal parameters by time of day in a healthy working population with high body-mass index - Özkunt, Okan; Sarıyılmaz, Kerim; Gemalmaz, Halil Cem (Turkish Spinal Surgery Society, 2018)
Object: To determine the change in spinal sagittal parameters which may occur throughout the day in healthy population with high body-mass index (BMI).Methods: Twenty-one healthy hospital employees with high BMI were enrolled in the study. Two standing left lateral ortho-roentgenograms were obtained at 8.00 a.m and at6.00 p.m. Six spinopelvic parameters were measured on the X-rays.Results: Twenty-one subjects with a mean age of 32.72± 7.84 were evaluated. No significant change was found between morning and evening measurements for any of the parameters. As a result of the correlation of daily changes for study parameters for the high BMI cohort showed significant direct relationship between SS and PI, LL and SS, LL and PI and an inverse relationship between LL and PI minus LL, SS and PI minus LL. (p < 0.05).Conclusion: Routine workload in a hospital environment does not cause significant change in the spinopelvic parameters throughout the day.
Keywords: Sagittal Balance; Change; Healthy; Collapse; Spinopelvic; Parameters